Factors Affecting Loan to Deposit Ratio at Regional Development Banks in Indonesia - Ernita Fatriawati (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2021)
The purpose of this study was to analyze the effect of Return on Assets (ROA), Capital Adequacy Ratio (CAR), Non-performing loans (NPLs), Net Interest Margin (NIM ), and Operating Expenses to Operating Income (OEOI) of the Loan to Deposit Ratio (LDR) to the Regional Development Bank in Indonesia. Population and sample in this research is the Regional Development Bank (BPD) in Indonesia, which is registered in the Financial Services Authority 2011-2016 period as many as 26 banks. The samples in this study using saturated sampling. The data analysis technique used is descriptive statistical analysis and regression of multiple panel data. Selection of panel data used is the Fixed Effects Model (FEM). The results of this study indicate that the Return on Assets (ROA) significant negative effect on the Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR) has negative and not significant to the Loan to Deposit Ratio (LDR), Non Performing Loans (NPLs) positive and not significant to the Loan to Deposit Ratio (LDR), Net Interest Margin (NIM) negative and not significant to the Loan to Deposit Ratio (LDR), and Operating Expenses to Operating Income (OEOI) negative and not significant to the Loan to Deposit Ratio (LDR). The predictive ability of these five variables against the Loan to Deposit Ratio (LDR) in this study amounted to 20.94%, while the remaining 79.06% influenced other variables not examined in this study. and Operating Expenses to Operating Income (OEOI) negative and not significant to the Loan to Deposit Ratio (LDR). The predictive ability of these five variables against the Loan to Deposit Ratio (LDR) in this study amounted to 20.94%, while the remaining 79.06% influenced other variables not examined in this study. and Operating Expenses to Operating Income (OEOI) negative and not significant to the Loan to Deposit Ratio (LDR). The predictive ability of these five variables against the Loan to Deposit Ratio (LDR) in this study amounted to 20.94%, while the remaining 79.06% influenced other variables not examined in this study.